The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1021/jm070271l
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Zn7Metallothionein with cis- and trans-[Pt(N-donor)2Cl2] Anticancer Complexes:  trans-PtII Complexes Retain Their N-Donor Ligands

Abstract: Intrinsic and acquired resistance are major drawbacks of platinum-based cancer therapy. The protein superfamily of cysteine- and ZnII-rich proteins, metallothioneins (MT), efficiently inactivate these antitumor drugs because of the strong reactivity of platinum compounds with S-donor molecules. In this study the reactions of human Zn7MT-2 with twelve cis/trans-[Pt(N-donor)2Cl2] compounds and [Pt(dien)Cl]Cl, including new generation drugs, were investigated and the products characterized. A comparison of reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
102
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 61 publications
5
102
0
Order By: Relevance
“…[265] Vasak et al reported on comparative studies of cis-and trans-based platinum complexes towards both Zn 7 MT-2 and Zn 7 -MT-3 using mass spectrometry amongst other techniques. [120,264] The difference between those two MTs is that the biosynthesis and expression of MT-2 are triggered by metal ions (amongst other compounds), whereas MT3 is not inducible. [120] In the case of MT-2, results showed that trans-platinum complexes react faster than the cis-ones.…”
Section: Metallothioneinsmentioning
confidence: 99%
See 3 more Smart Citations
“…[265] Vasak et al reported on comparative studies of cis-and trans-based platinum complexes towards both Zn 7 MT-2 and Zn 7 -MT-3 using mass spectrometry amongst other techniques. [120,264] The difference between those two MTs is that the biosynthesis and expression of MT-2 are triggered by metal ions (amongst other compounds), whereas MT3 is not inducible. [120] In the case of MT-2, results showed that trans-platinum complexes react faster than the cis-ones.…”
Section: Metallothioneinsmentioning
confidence: 99%
“…[120,264] The difference between those two MTs is that the biosynthesis and expression of MT-2 are triggered by metal ions (amongst other compounds), whereas MT3 is not inducible. [120] In the case of MT-2, results showed that trans-platinum complexes react faster than the cis-ones. Characterization of the adducts revealed that in the case of the cis-Pt(II) compounds, all initial ligands were replaced by cysteine residues, whereas trans-Pt(II) complexes were found to retain their N-donor ligands, thus remaining in a potentially biologically active form.…”
Section: Metallothioneinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The merged band changed from orange to red after 4 h (Figure 3I), suggesting platination of FAM-G15. Therefore, an interesting effect of citrate is to increase the selectivity of cisplatin towards guanine compared to adenine, 15 which might have implications for guanine being the eventual target of cisplatin. [37][38][39] In summary, we employed fluorescently-labeled oligonucleotides for studying the reaction between cisplatin and DNA.…”
mentioning
confidence: 99%